Effects of Graphene Quantum Dots on the Self‐Renewal and Differentiation of Mesenchymal Stem Cells. Issue 6 (2nd February 2016) - Qiu, Jichuan; Li, Deshuai; Mou, Xiaoning; Li, Jianhua; Guo, Weibo; Wang, Shu; Yu, Xin; Ma, Baojin; Zhang, Shan; Tang, Wei; Sang, Yuanhua; Gil, Pilar Rivera; et al.
Abstract : The influence of graphene quantum dots (GQDs) on key characteristics of bone marrow derived mesenchymal stem cells (MSCs) phenotype (i.e., self‐renewal, differentiation potential, and pluripotency) is systematically investigated in this work. First, the viability and impact of GQDs on the self‐renewal potential of MSCs is evaluated in order to determine a threshold for the exposing dose. Second, GQDs uptake by MSCs is confirmed due to the excellent fluorescent properties of the particles. They exhibit a homogenous cytoplasmatic distribution that increases with the time and concentration. Third, the impact of GQDs on the osteogenic differentiation of MSCs is deeply characterized. An enhanced activity of alkaline phosphatase promoted by GQDs indicates early activation of osteogenesis. This is also confirmed upon GQD‐induced up‐regulation of phenotypically related osteogenic genes (Runx2, osteopontin, and osteocalcin) and specific biomarkers expression (osteopontin and osteocalcin). GQDs also effectively enhance the formation of calcium‐rich deposits characteristics of osteoblasts. Furthermore, genes microarray results indicate that the enhanced osteogenic differentiation of MSCs by GQDs is in progress through a bone morphogenetic protein and transforming growth factor‐β relative signaling pathways. Finally, intracytoplasmatic lipid detection shows that GQDs can also promote the adipogenic differentiation of MSCs, thus confirming the prevalence of their pluripotency potential. Abstract : Interactions between graphene quantum dots (GQDs) and mesenchymal stem cells (MSCs) are investigated in a systematic way. Good fluorescent property of GQDs facilitates the observation of GQDs uptake by MSCs. Within a certain range of concentration, GQDs have no significant influence on self‐renewal potential of MSCs, but even promote and enhance their osteogenic and adipogenic differentiation at the level of mRNA and protein expression.